The Rac-GEF Tiam1 controls integrin-dependent neutrophil responses - Hornigold, Kirsti; Baker, Martin J.; Machin, Polly A.; Chetwynd, Stephen A.; Johnsson, Anna-Karin; Pantarelli, Chiara; Islam, Priota; Stammers, Melanie; Crossland, Laraine; Oxley, David; Okkenhaug, Hanneke; Walker, Simon; et al. (Frontiers in Immunology, 2023)
Rac GTPases are required for neutrophil adhesion and migration, and for the neutrophil effector responses that kill pathogens. These Rac-dependent functions are impaired when neutrophils lack the activators of Rac, Rac-GEFs from the Prex, Vav and Dock families. In this study, we demonstrate that Tiam1 is also expressed in neutrophils, governing focal complexes, actin cytoskeletal dynamics, polarisation and migration, in a manner depending on the integrin ligand to which the cells adhere. Tiam1 is dispensable for the generation of reactive oxygen species but mediates degranulation and NETs release in adherent neutrophils, as well as the killing of bacteria. In vivo, Tiam1 is required for neutrophil recruitment during aseptic peritonitis and for the clearance of Streptococcus pneumoniae during pulmonary infection. However, Tiam1 functions differently to other Rac-GEFs. Instead of promoting neutrophil adhesion to ICAM1 and stimulating β2 integrin activity as could be expected, Tiam1 restricts these processes. In accordance with these paradoxical inhibitory roles, Tiam1 limits the fMLP-stimulated activation of Rac1 and Rac2 in adherent neutrophils, rather than activating Rac as expected. Tiam1 promotes the expression of several regulators of small GTPases and cytoskeletal dynamics, including αPix, Psd4, Rasa3 and Tiam2. It also controls the association of Rasa3, and potentially αPix, Git2, Psd4 and 14-3-3ζ/δ, with Rac. We propose these latter roles of Tiam1 underlie its effects on Rac and β2 integrin activity and on cell responses. Hence, Tiam1 is a novel regulator of Rac-dependent neutrophil responses that functions differently to other known neutrophil Rac-GEFs.